Pengaruh Pemberian Jus Buah Naga Merah (Hylocereus polyrhizus) Terhadap Kadar Trigliserida Tikus Putih (Rattus norvegicus) Hiperlipidemia - Rizqi, Afrida Wira Surya; Widada, Subrata Tri; Martsiningsih, M Atik (POLTEKKES KEMENKES YOGYAKARTA, 2014)
Cardiovascular disease is a disease that causes the most deaths in the world. One of its main risk factor is triglyceride levels which make the emergence of plaque in coronary artery. Statin as an option drug in reducing triglyceride levels apparently reported to cause myopathy and kidney failure when used in a long term. Natural product like red dragon fruit began to be developed as a safer alternative. The content of various substances such as niacin, vitamin C and fiber in it useful as antihypertriglyceridemia.This study aims to determine the effect of red dragon fruit (Hylocereus polyrhizus) juice to the decrease of triglyceride levels in hyperlipidemic white rats (Rattus norvegicus).This study was an experimental study with pre and post test with control group design. The subjects were 24 male experimental animals (Rattus norvegicus) were divided into 4 groups: one positive control group given simvastatin 0.18 mg/ 200 gram of weight and three groups treated with red dragon fruit juice doses of 3.6; 5.4 and 7.2 gram/ 200 gram of weight. Then, data were analyzed descriptively with One-Way ANOVA test using SPSS 16.0 for Windows.Results with descriptive analysis obtained that mean of positive control’s pre-test triglyceride level was 104.80 mg/ dl and treatment groups I, II and III respectively 108.15 mg/ dl, 106.47 mg/ dl and 107.43 mg/ dl whereas positive control’s post-test triglyceride level was 51.09 mg/ dl and for the treatment groups were 94.64 mg /dl, 71.01 mg/ dl and 58.75 mg/ dl. One Way ANOVA test obtained p <0.05 which indicated the difference between the treatment of various doses of red dragon fruit juice to white rats’ triglyceride levels. Based on that, means there is the effect of various doses of red dragon fruit (Hylocereus polyrhizus) juice to the decrease of triglyceride levels in hyperlipidemic white rats (Rattus norvegicus).